Functions and relevance of spatial co-presence: Lessons learned from the COVID-19 pandemic for evidence-based workplace and human capital management - Windlinger, Lukas; Gerber, Marius (Frontiers in Built Environment, 2023)
This study aims to analyze the role of co-presence against the background of COVID-19 pandemic to derive implications for an interdisciplinary, evidence-based workplace and human capital management. A theoretical framework is outlined that considers a range of topics from task performance to social and organizational contextual factors. In a single organization qualitative case study, five focus group interviews including a total of 19 employees of an IT consultancy were conducted to identify the effects of the mandatory remote working regimes imposed by the COVID-19 Pandemic on task and contextual performance. Results show that individual performance was assessed to have increased while internal processes remained at similar levels compared to pre-pandemic levels. Organizational culture, social contact, and identity, however, were reported to have considerably deteriorated in the view of the participants. The study shows that for a company that was very experienced with distributed working, the reduction of co-presence had important effects on performance and culture. Findings suggest that copresence must be carefully managed in the future. This could become a new joint priority for workplace design, workplace management, and human capital management.